(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This paper aims to investigate the circulation of Lamb waves in a transversely isotropic, homogeneous thermoplastic solid plate in the context of the non-classical theories of thermo-elasticity. The surfaces of the solid plate are added with the finite thickness of non-viscous fluid layers on both sides with varying temperatures. Helmholtz decomposition technique is used to find out the solutions. After developing the mathematical model, formal solution, and boundary conditions, the frequency equations are derived for a homogeneous, transversely isotropic solid plate for both symmetric and asymmetric modes. Some regions of frequency equations are deduced depending on the characteristic roots. The numerical simulation is prepared for a transversely isotropic zinc material plate cladded with water and represented graphically. The theoretical and numerical computations are found to be in close agreement.